2018
DOI: 10.1159/000488530
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Potassium-Competitive Acid Blocker-Resistant Non-Erosive Reflux Disease

Abstract: Background: The present study examined the pathogenesis of potassium-competitive acid blocker (P-CAB)-resistant non-erosive reflux disease (NERD). Methods: Forty-three patients with NERD, who had persistent reflux symptoms despite the administration of P-CAB, were included in this study. After excluding eosinophilic esophagitis and primary esophageal motility disorders, esophageal impedance-pH monitoring was performed. In symptom index (SI)-positive patients, the mechanism of SI-positivity and percent time wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Regarding correlation between changes in FSSG score from 8 weeks after treatment or discontinuation to before treatment and OTE, correlations were found between total FSSG score and OTE, and between FSSG RS score and OTE (total FSSG vs. OTE: r = 0.857, P = 0.0017; FSSG RS vs. OTE: r = 0.857, P = 0.0017) ( Figure 7). Contrarily, in a previous study, no patients had symptoms caused by acid reflux on administration of P-CAB 6 . Therefore, patients with functional heartburn can be more readily selected from those with P-CAB-resistant NERD.…”
Section: Correlation Between Changes In Fssg Score and Otementioning
confidence: 71%
See 1 more Smart Citation
“…Regarding correlation between changes in FSSG score from 8 weeks after treatment or discontinuation to before treatment and OTE, correlations were found between total FSSG score and OTE, and between FSSG RS score and OTE (total FSSG vs. OTE: r = 0.857, P = 0.0017; FSSG RS vs. OTE: r = 0.857, P = 0.0017) ( Figure 7). Contrarily, in a previous study, no patients had symptoms caused by acid reflux on administration of P-CAB 6 . Therefore, patients with functional heartburn can be more readily selected from those with P-CAB-resistant NERD.…”
Section: Correlation Between Changes In Fssg Score and Otementioning
confidence: 71%
“…Functional heartburn is a cause of proton pump inhibitor (PPI)resistant NERD, and it was reported that around 20%-50% of patients with PPIresistant NERD have functional heartburn [2][3][4][5] . Additionally, approximately half of NERD patients who are resistant to potassium-competitive acid blocker (P-CAB) (novel and potent acid secretion inhibitor), and whose symptoms do not improve, have functional heartburn [6][7][8] . Although the pathophysiology of functional heartburn is unclear, the appearance symptoms is not triggered by reflux.…”
Section: Introductionmentioning
confidence: 99%
“…The newly developed potassium-competitive acid blocker vonoprazan has a much greater ability to suppress gastric acid production than conventional PPIs [16,17], and as expected, vonoprazan has shown strong efficacy for treating GERD in clinical practice in Japan. In the present study, we examined whether or not there was any marked difference in the proportion of underlying disease conditions between conventional PPI-and vonoprazan-resistant GERD in clinical practice by performing both HRM and MII-pH monitoring [11,18]. We subsequently observed a significant difference in the proportion of underlying disease conditions between these 2 types of resistant GERD.…”
Section: Discussion/conclusionmentioning
confidence: 95%
“…Vonoprazan has the potential to normalize the oesophageal acid exposure time (AET) in GERD patients and cure acid-related EE and NERD [9,10]. It was recently reported that symptoms related to acid reflux might be ruled out by vonoprazan [11], but further evidence is yet needed before it can be applied to clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that switching to P-CAB from conventional PPIs achieved high mucosal healing rates in patients with PPI-refractory reflux esophagitis [6,7]. However, even with the use of P-CAB, NERD patients refractory to P-CAB therapy still exist and the pathogenesis of these patients was complex [8]. These data mean that acid reflux has only a minor effect on the pathophysiologic mechanism of NERD.…”
Section: Introductionmentioning
confidence: 99%